Dynamic stratified porosity computation from canopy interaction simulation between airflow and leaves - Cui, Huiyuan; Wang, Chengde; Lu, Fadian; Liu, Xuemei; Yuan, Jin (Frontiers in Plant Science, 2023)
The main goal of wind-driven spraying is to use assisted airflow to disrupt the structure of branches and leaves and broaden the air delivery channel, so as to achieve uniform droplet deposition in the middle and lower parts of the canopy. Due to the complex branch and leaf structure inside the canopy, there is currently no effective method to express the dynamic changes of canopy porosity and the law of airflow attenuation under assisted airflow. In this study, based on the two-way fluid-structure interaction numerical simulation method, the relating between the assisted airflow and the structural parameters of the cotton canopy is analyzed, and a new method for predicting and simulating the dynamic porosity of the canopy is proposed. Firstly, a two-way fluid-structure interaction model based on Lattice Boltzmann (LB) solver and Finite Element (FE) solver is developed to simulate the deformation motion of cotton leaves and the spatial distribution of airflow field, and the correctness of the numerical simulation is verified based on indoor measurement data. Secondly, the post-processing method of Computational Fluid Dynamics (CFD) is used to obtain images of leaves at different canopy positions under assisted airflow, and the porosity changes are calculated and analyzed by image processing. The research results show that under different initial wind speeds (5 m·s-1, 10 m·s-1, 15 m·s-1), the maximum normalized mean absolute error (NMAE) between the simulated values and the measured values is 13.99%, 20.72% and 16.08%, respectively. The coefficient of determination (R2) for linear fitting between simulated values and measured values is 0.9221. These validation results indicate the effectiveness of the numerical simulation method. The validated CFD model is applied to predict leaf deformation and porosity changes within the canopy under various wind loads and times. The application results have well revealed the interaction between crop leaves and airflow, and will be beneficial to make a better understanding of the effect of assisted airflow on droplet deposition.